2020
DOI: 10.1016/j.enbuild.2019.109582
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mean radiant and air temperatures in mechanically-conditioned commercial buildings from over 200,000 field and laboratory measurements

Abstract: We assessed the difference between mean radiant temperature (! ) and air temperature (! ) in conditioned office buildings to provide guidance on whether practitioners should separately measure ! or operative temperature to control heating and cooling systems. We used measurements from 48 office buildings in the ASHRAE Global Thermal Comfort Database, five field studies in radiant and all-air buildings, and five test conditions from a laboratory experiment that compared radiant and all-air cooling. The ASHRAE G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 24 publications
4
28
0
Order By: Relevance
“…According to CIBSE guide A [40], "in well insulated rooms and away from direct radiation from the sun or from other high temperature radiant sources, the difference between air and the mean radiant temperatures (and hence between the air and operative temperatures) is small". The on-site measurements, done by Dawe et al [74] and Walikewitz et al [75], also show that in the absence of a radiative heat source or sink (e.g., radiative heating or cooling system, windows facing south-east and south-west), the air temperature can be used as an estimation of radiant and consequently operative temperature as the difference is around 0.4-0.5 K. Based on that, it can be assumed that the operative temperatures in the CSET building are in proximity to the measured air temperatures. The results are summarized in Figure 7.…”
Section: Data From Sensors and Analysismentioning
confidence: 99%
“…According to CIBSE guide A [40], "in well insulated rooms and away from direct radiation from the sun or from other high temperature radiant sources, the difference between air and the mean radiant temperatures (and hence between the air and operative temperatures) is small". The on-site measurements, done by Dawe et al [74] and Walikewitz et al [75], also show that in the absence of a radiative heat source or sink (e.g., radiative heating or cooling system, windows facing south-east and south-west), the air temperature can be used as an estimation of radiant and consequently operative temperature as the difference is around 0.4-0.5 K. Based on that, it can be assumed that the operative temperatures in the CSET building are in proximity to the measured air temperatures. The results are summarized in Figure 7.…”
Section: Data From Sensors and Analysismentioning
confidence: 99%
“…It also demonstrates that the radiant system was able to maintain consistent indoor temperatures as the HVAC modes switched. In addition, the median infrared and dry-bulb temperature measured in the occupied zone by our sensor kits were 22.6 °C and 22.8 °C, respectively, indicating that there are negligible differences in air and mean radiant temperatures experienced by occupants in this building (Dawe et al 2020). The subjective thermal satisfaction responses from the small number of subjects indicate that this radiant building exceeds the ASHRAE 80% acceptability criteria ( Figure 5).…”
Section: Subjective and Ieq Measurementsmentioning
confidence: 76%
“…Differences between and were small for most floors-less than 0.5°C-with T a T o greater variance in than . An analysis [51] of field measurements in ASHRAE Global T a T o Thermal Comfort Database II [52] and additional laboratory testing reported similar differences in air and radiant temperatures, and they suggested as an appropriate estimate of mean T a radiant temperature when it is not readily available. Moreover, recent studies have reported systematic errors when using traditional globe thermometers to measure radiant temperature [53,54].…”
Section: Use Of Air or Operative Temperaturementioning
confidence: 97%